(3LhGeY cJGH LGdjfhS aj GdCeQGV GdMGOKI aj GdYjfs - (3LGdjfhSs
(3ChdgG (B:s
(3CeQGV GdLaf SJI YTQ eQVkG (B: (3GdLQH hGdHQO hGdJMLQdEdJRGb GdTYjQg hGdTYQ GdRGFO s
(3BNQgG (B:s
(3hai GdeTjeI KeGfjI , hai GdRLGLjI KeGfjI , hai GdUdHI KeGfjI, aPdc CMO hJSYhf eQVkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B78 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH JjehQ (B100) s
Keywords: (3GdWHs